2021
DOI: 10.28991/cej-2021-03091730
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Grain Size and Distribution on Mechanical Behavior of Dune Sand

Abstract: Sand is a major component of soils. It is widely used in manufacturing and construction. In geomechanics, one characterizes sand according to various aims. This paper investigates, for local sands, the effect of grain size and granular distribution on the mechanical behavior in terms of strength and stress-strain relationship. For this purpose, dune sands of the great Occidental Erg, from Algeria, are analyzed, according to the Mohr-Coulomb criterion. The study uses three kinds of sands. Every kind is divided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…When the normal stress is 100 kPa and 200 kPa the residual stress shows stability at large displacement. The peak shear strengths increase with the increase in applied normal stress that makes the sands denser in the higher normal stress, this is in agreement with the previous studies of dune sand (Boudia & Berga, 2021).…”
Section: Testing Procedures and Programsupporting
confidence: 92%
“…When the normal stress is 100 kPa and 200 kPa the residual stress shows stability at large displacement. The peak shear strengths increase with the increase in applied normal stress that makes the sands denser in the higher normal stress, this is in agreement with the previous studies of dune sand (Boudia & Berga, 2021).…”
Section: Testing Procedures and Programsupporting
confidence: 92%
“…The results of undrained monotonic triaxial compression tests obtained by Mahmoudi et al [21] indicate that the use of the global void ratio approach induces significant effects on the mechanical behavior, they showed that the plastic fines content up to the limit fines content seems to be a reliable parameter to be considered in the characterization of the mechanical response of sand and silt mixtures. Boudia et al [22] have treated the effect of grain size and granular distribution of local sands on the mechanical behavior in terms of strength and stress-strain relationship. Results show an increase in peak friction angle with the increase of particles size and they consider sands as a purely cohesive material.…”
Section: Introductionmentioning
confidence: 99%